The ambiguities of the historiciza tion of violence in Argentina and Chile (Andamios, Revista de Investigación Social, 2012)
Historicizing dictatorial violence and its consequences postdictatorial is one of the most debated analytical work have been raised in Argentina and Chile, which have focused various social discourses, suchas historiographical, legal yel critical thinking in general. Despite the multiplicity of approaches to this intellectual challenge, there is a social context determines that there is a way discursivadesa production from which is reproduced a number of topics that are used implicitly or explicitly to explain the period.
Keywords: Argentina historiography; historiography chilean; dictatorship and post-dictatorship; memory; violence